THE EFFECT OF GIVING EARTHWORMS (Lumbricus rubellus) FEED DIFFERENT FEEDING FREQUENCY TOWARD THE OVULATION AND HATCHING RATE OF SIBAN (Cyclocheilichthys apogon Val. 1842) EGGS - Monalisa Monalisa; Nuraini Nuraini; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted on April until June 2017 in Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine University of Riau. The aim of this research was to know the effect of giving earthworms (Lumbricus rubellus) feed with different feeding ferequency toward the ovulation and hatching rate of siban (Cyclocheilichthys apogon val. 1842) eggs. The method in this research was an experimental method with Completely Randomized Design (CRD) with one factor, four treatments and three replications. The treatment in this research were P0 (the giving pellets as a control feed with frequency three times a day), P1 (the giving Earthworms (Lumbricus rubellus) with frequency twice times a day), P2 (the giving Earthworms (Lumbricus rubellus) with frequency three times a day), P3 (the giving Earthworms (Lumbricus rubellus) with frequency four times a day). The results showed that the best treatment was in P3 (the giving Earthworms (Lumbricus rubellus) with frequency four times a day) which produce latent time 4 hours 9 minutes, the number of eggs the striping average of 76 grains/gram of parent, fertilization rate of 73,20%, hatching rate average of 86,45% and survival rate of larvae average of 83,02%. Keyword : Cyclocheilichthys apogon Val. 1842, Earthworms (Lumbricus